Comics as a didactic resource for teaching and learning marketing (Research, Society and Development, 2023)
One of the challenges of teaching marketing is the use of strategies and didactic resources that promote active and meaningful learning about the reality of the market and contemporary marketing. Based on this context, this article aims to present a proposal for the use of comics as a didactic resource for teaching and learning marketing topics in the classroom. To meet this objective, a process was developed that describes a set of tasks that can be followed in the classroom and contextualized according to the reality and content of each discipline. The process in question was elaborated based on the analysis of the literature on the subject and also based on experiences in the classroom that show the viability of the proposal. Associating the creation of comics with marketing teaching and learning is one of the main contributions of the work, as it indicates the potential of using this didactic resource for active and meaningful learning on the subject. It also characterizes a contribution of the study, the conception of a process that can be adapted in higher education, providing the elaboration of comics about marketing in the classroom. The use of comics can be a playful strategy, capable of attracting and stimulating students to study marketing topics, thus promoting motivation, interaction and engagement, as opposed to merely lectures and monologues.